Characterization of a mutation in a strain of Penicillium camembertii affecting the production of cyclopiazonic acid - R. Geisen (Fungal Genetics Reports, 1992)
Penicillium camembertii is a filamentous fungus used for the production of mold- fermented white cheese. It is a domesticated form of Penicillium commune, especially adapted to the food environment (Pitt et al. 1986. Food Microbiol. 3:363-371). Despite its use as food starter culture, P. camembertii is able to produce cyclopiazonic acid (CA), a secondary metabolite toxic to animals and humans (Holzapfel 1968. Tetrahedron 24:2101- 2119); Le Bars 1979. Appl. Environ. Microbiol. 38:1052-1055). The synthesis of CA starts from the amino acid tryptophan with the condensation of acetyl-CoA and isoprenoids, especially dimethyl allylpyrophosphate (Holzapfel 1980. In: P.S. Steyn, The biosynthesis of mycotoxins, Academic Press). Acetyl-CoA is also the direct precursor of the isoprenoids